The political economy of monetary reform - Aliber, Robert Z. (London : Macmillan, 1977)
This volume is a collection of the papers presented at the Summer-I974 conference at Racine, Wisconsin, dealing with interrelationships between national monetary policies and the international monetary order. The editor, R. Z. Aliber, has divided the papers into three groups: those dealing with institutional issues of international monetary order; those dealing with theory; and those dealing with empirical evidence. The Mahar-Porter and Parkin papers, though, probably belong in the theoretical section rather than the empirical one.
Proceedings of a conference held at Racine, Wisconsin, 1974.
Includes bibliographies and index.
usc 16/04/2018
Loans
Keywords: International finance; Monetary policy